2021
DOI: 10.1186/s12863-021-01008-8
|View full text |Cite
|
Sign up to set email alerts
|

The effects of habitat fragmentation on the genetic structure of wild boar (Sus scrofa) population in Lithuania

Abstract: Background Wild boar (Sus scrofa) is a widely distributed ungulate whose success can be attributed to a variety of ecological features. The genetic variation and population structure of Lithuania’s wild boar population have not yet been thoroughly studied. The purposes of this study were to investigate the genetic diversity of S. scrofa and assess the effects of habitat fragmentation on the population structure of wild boar in Lithuania. A total of 96 S. scrofa individuals collected from differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 41 publications
3
9
1
Order By: Relevance
“…Even with a recent reconnection, the two hypothetic clusters would still be visible, and we would have three main types of individuals distributed along the ecological corridor: individuals from the first cluster, individuals from the second cluster, and admixed individuals due to reproduction between the two previously separated clusters. In congruence with our results, analogous studies on wild boar population structures at the landscape scale found no genetic differentiation resulting from motorway separation [29,78,79], with fencing since 2004 [29] and with >20,000 average users/day [29,78]. It was suggested that genetic clustering effects were rather due to isolation-by-distance [30], or to the species' characteristics or recolonization history [31].…”
Section: Population Differentiationsupporting
confidence: 88%
See 1 more Smart Citation
“…Even with a recent reconnection, the two hypothetic clusters would still be visible, and we would have three main types of individuals distributed along the ecological corridor: individuals from the first cluster, individuals from the second cluster, and admixed individuals due to reproduction between the two previously separated clusters. In congruence with our results, analogous studies on wild boar population structures at the landscape scale found no genetic differentiation resulting from motorway separation [29,78,79], with fencing since 2004 [29] and with >20,000 average users/day [29,78]. It was suggested that genetic clustering effects were rather due to isolation-by-distance [30], or to the species' characteristics or recolonization history [31].…”
Section: Population Differentiationsupporting
confidence: 88%
“…Studies yield various results by using the STR genetic profiling method to uncover the effect of urbanization on the population structure of wild boars. On the one hand, it was shown that motorways in Belgium and Lithuania did not represent a significant limitation to gene flow (i.e., migration between regions with successful reproduction) [28,29]. Two studies suggest that most of clustering effects were due to characteristics and recolonization history of the species [30], or to the isolation-by-distance [31], rather than to the landscape features or the urbanization coverage.…”
Section: Introductionmentioning
confidence: 99%
“…The analysis of genetic diversity and the population structure of wild boars was conducted with regard to the different prevalence estimates of ASF in affected areas of the country. This study aimed to extend the previous study [ 24 ] and obtain more insight into changes in the genetic structure of the wild boar population in Lithuania following the emergence of ASF. In the previous study, in which 15 microsatellites were analysed, no evidence was found of genetic differentiation among wild boars before the ASF outbreak in Lithuania [ 24 ].…”
Section: Discussionmentioning
confidence: 95%
“…This study aimed to extend the previous study [ 24 ] and obtain more insight into changes in the genetic structure of the wild boar population in Lithuania following the emergence of ASF. In the previous study, in which 15 microsatellites were analysed, no evidence was found of genetic differentiation among wild boars before the ASF outbreak in Lithuania [ 24 ].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation